(untitled) (Journal of International Studies, 2020)
The main purpose of this study is to highlight the absence of specific provisions on public health under Article 31bis of the TRIPS Agreement that were not incorporated into the Patents Act 1983 in Malaysia. The main research question of this study is; why should Malaysia immediately amend its Patents Act 1983 to incorporate these flexibilities? Malaysia must develop effective strategies to implement policies, law and governance in managing the country’s public health system. This is to ensure that the balance of rights between intellectual property owners and the public is maintained at all times. This study employs a qualitative research methodology that is based on primary sources such as the TRIPS Agreement and the Patents Act 1983, and is further supported by secondary sources such as journals and the contents of authorities’ websites. This study is limited to the issues related to public health and patents. This study includes a discussion on the provisions related to patents and public health, proposed amendments to the Patents Act 1983 that should incorporate the provisions from Article 31bis, and a conclusion was presented on the importance of immediately amending the Patent Act 1983 to incorporate these provisions, particularly during the current Covid-19 pandemic. This study proposes that the amendments must be made to Section 84 of the Patents Act 1983 with respect to Rights of Government, and not through the compulsory licence mechanism under Part X of the Patents Act 1983. Thus, this study concludes that currently, Malaysia is unable to implement the provisions under Article 31bis, unless the Patents Act 1983 is amended.